(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
This work evaluates the central nervous effects in ICR strain mice of 2-ethylthio-7-methyl-4-(4-methylphenyl)pyrazolo[1,5-a][1,3,5]triazine (MH4b1), a compound obtained by an efficient one-step reaction of S,S-diethyl 4-methylbenzoylimidodithiocarbonate with 5-amino-3-methyl-1H-pyrazole, in order to assess its neuro-pharmacological profile. The tests applied were: maximal electroshock seizure (MES), pentylenetetrazole (PTZ) seizures, forced swimming, plus maze, marble burying, sleeping time, rota-rod and catalepsy. In addition, MH4b1 binding to the benzodiazepine site of the GABA-A receptor and MH4b1 inhibition of monoamine oxidase (MAO) subtypes A and B were evaluated. MH4b1 showed anticonvulsant effects in a dose dependent manner (30-300 mg/kg, p.o.) against MES and inhibition of MAO-B (IC50: 24.5 µM) without activity at the benzodiazepine site. These data suggest that MH4b1 has anticonvulsant properties related to MAO-B inhibition.